Characteristics of Polyurethane Cross-Laminated Timber Made from a Combination of Pine and Coconut - Baskara, Muhammad Iqbal Adi; Hadi, Yusuf Sudo; Lubis, Muhammad Adly Rahandi; Maulana, Muhammad Iqbal; Sari, Rita Kartika; Febrianto, Fauzi; Hidayat, Wahyu (Jurnal Sylva Lestari, 2023)
The objective of this study was to assess the properties of cross-laminated timber (CLT) fabricated from the combination of Sumatran pine (P) and coconut trunk (C) bonded with polyurethane adhesive. The basic properties of raw materials and adhesives were characterized. The CLT panels’ length, width, and thickness are 100 cm by 30 cm by 3.6 cm, respectively. Three-layer CLT was made with 4 combinations of face/core/back lamina, i.e., PPP, CCC, PCP, and CPC, which are arranged perpendicular to each other. The laminae were bonded using PU adhesive on 160 g.m-2 glue spread. The CLT’s delamination and wood failure percentages (WFP) were assessed following the JAS 3079 (2019) standard. The study’s results demonstrated that the PU adhesive employed in this investigation could curl ideally at 30°C for 200 min. Solid pine and coconut’s physical and chemical characteristics differed, but their wettability to polyurethane adhesives was identical. Hybrid pine CLT has greater attributes compared to single pine CLT. Single coconut CLT, on the other hand, offers better features than hybrid coconut CLT. All CLT samples failed to fulfil the JAS 3079 (2019) requirement for delamination (=< 10%) and WFP (>= 90%). Keywords: Coconut trunk, cross-laminated timber, layer combination, pine wood, polyurethane adhesive